2019
DOI: 10.1063/1.5079748
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-induced competitive two-site binding

Abstract: Note: This article is part of the Special Topic "Markov Models of Molecular Kinetics" in J. Chem. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…22 However, this modest drop in rate constant is not necessarily indicative of the encapsulin shell as a rate-determining barrier to diffusion, as for example, competition between multiple encapsulated LBTs within the encapsulin lumen could also result in complex kinetics that can lower the apparent first-order rate. 47,48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, this modest drop in rate constant is not necessarily indicative of the encapsulin shell as a rate-determining barrier to diffusion, as for example, competition between multiple encapsulated LBTs within the encapsulin lumen could also result in complex kinetics that can lower the apparent first-order rate. 47,48…”
Section: Resultsmentioning
confidence: 99%
“…22 However, this modest drop in rate constant is not necessarily indicative of the encapsulin shell as a rate-determining barrier to diffusion, as for example, competition between multiple encapsulated LBTs within the encapsulin lumen could also result in complex kinetics that can lower the apparent first-order rate. 47,48 Furthermore, all pore variants exhibited relatively similar slow rate constants for Tb 3+ turn-on kinetics (Figure 4c, SI Figure S7.1), suggesting that the overall kinetics may primarily be governed by Tb 3+ -LBT luminescent complex formation as a rate-determining step, rather than transit through the pores. Apart from S3E and S6E which showed slight increases over the wild-type rate with pseudo-first order rate constants of 55±3 s -1 and 70±4 s -1 respectively, there were minimal differences in rate for the remainder of the variants, including the S7G control featuring a wide but positively-charged five-fold pore (46±2 s -1 ), which had previously been reported to give a seven-fold increase in Tb 3+ flux using a comparable experimental setup.…”
Section: Overall Reaction Kinetics Depends On Whether Influx or Cargo Kinetics Is Rate Determiningmentioning
confidence: 94%
“…The effective affinity is likely to be raised through both an increase in the number of productive encounters given the high density of SLiMs, and through rebinding mechanisms that reduce the diffusion of Calcineurin away from the scaffold since the molecule is likely to be intercepted by another binding site rather than diffusing away. We note that a recently developed model for competitive two-site binding showed that the bound population at one site can influence kinetics of binding at the other where they are connected by a diffusion pathway (39). This latter point is borne out directly in our experiments by the lack of complete dissociation of Calcineurin on AKAP5c seen by SPR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in an article, Szabo et al investigated the effect of ligand diffusivity on the reversible binding kinetics of a ligand to a macromolecule with two distinct competitive binding sites. In the fast diffusion limit, the two sites behave quite independentlyoccupancy of a ligand to one site is independent of the other; thus, the reaction network follows the ordinary chemical kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…We present the rate equations associated with reversible ligand binding to a macromolecule with two competitive binding sites within Markovian Wilemski–Fixman approximation in Section of the Methods section. This sub-section is basically a recapitulation of Szabo et al’s paper, which we need to keep for the sake of completeness. The effects of ligand diffusion on the precision of single site occupancy, the mean dynamical activity, and the mean entropy production rate are calculated in Section .…”
Section: Introductionmentioning
confidence: 99%